PENGGUNAAN MEDIA POSTER DALAM LAYANAN BIMBINGAN KONSELING UNTUK MEMBANTU PESERTA DIDIK MERENCANAKAN KARIR - Wahyu Sri Widiyastuti (STKIP PGRI SUMENEP, 2023)
The purpose of this study is to reach the truth of the research data from the title Use of poster media to help students plan their careers. The method used is descriptive qualitative method sourced from secondary data in the form of literature studies. In this study, the use of website-based poster media to support a counseling guidance teacher helps provide information services to students regarding career choices after graduating from high school. In addition, technological developments can also help students improve career planning and maturity, if used properly. Media itself is one of the learning media that can be a source of learning in instructional activities. One of the media that can be used by the counsellor's guidance teacher for giving lessons is a website-based poster media. The selection of poster media as a career guidance service media here is one of the reasons because posters can attract readers by producing interesting pictures and writings.